A Clinical Case of Prosthetic Treatment After Orthodontic Extrusion Using a Removal Denture as Anchorage - Ogami, Koichiro (Nihon Hotetsu Shika Gakkai Zasshi, 2007)
Patient: A 73-years-old male complained of food stuffing for at anterior tooth and aesthetic disturbance. The diagnosis was stagnation of food which occurred to 3/3 secondary caries and aesthetic disturbance caused by non-conformity of the margin. After extraction of135, an immediate denture (5+5) was inserted. In addition, 3 was extruded by removal the partial denture as an anchorage. Discussion: The clasp of the upper first molar was broken three years after prosthetic treatment. After that, there has been no specific trouble. Conclusion: Removal of the partial denture was used as an anchorage to apply the orthodontic extrusion method over the maxillary left side canine. Through this method, we were able to perform conservative procedures for the treatment of the deep caries lesion observed on this tooth. Once the extrusion was completed, we could restore this tooth through prosthetic treatment. Long term good results were achieved.